Elastoplastic analysis of surrounding rock in weakly cemented soft rock roadways and its support practice - Jihua Zhang; Qiao Rui; Xinwei Li; Yushun Yang; Ge Wang; Jiarui Chen; Wei Shen; Chengwu Wang; Weili Liu (Scientific Reports)
Abstract The effects of rock softening and shear dilation in the plastic zone are considered to examine the stability of the surrounding rock in deeply buried and weakly cemented soft rock roadways. An elastic-soft fracture mechanical model of the surrounding rock is developed, from which the analytical solutions for the stress and displacement fields are derived, providing expressions for the radius of the plastic zone. This analysis assesses the impact of initial cohesion, internal friction angle, and support force on the stress field, displacement field, and plastic zone radius. The results indicated that the elastic–plastic mechanical model, which considers the softening and shear dilation effects, more accurately represents the deformation characteristics of the roadway’s surrounding rock across the zones of elasticity, softness, and fragmentation. As initial cohesion and internal friction angle increase, the surrounding rock’s load resistance is enhanced, delaying the emergence and expansion of plastic zones. The elastic–plastic interface moves toward the excavation surface, causing a gradual increase in the circumferential stress at the interface. With increasing initial cohesion and internal friction angle, the radius of the plastic zone exhibits a non-linear decrease, with the plastic fracture zone diminishing first. The influence of initial cohesion and internal friction angle on the various zones of surrounding rock is ranked as follows: radius of plastic fracture zone > plastic softening zone > elastic zone. A joint support scheme, incorporating “anchor net and cable injection” with grouting as the core component, is proposed for a project overview of weakly cemented soft rock roadways in the western mining area. This scheme achieves positive outcomes and enhances the safety of roadway construction.